ANALISIS FAKTOR PENENTU YANG MEMPENGARUHI MINAT WIRAUSAHA MAHASISWA STIE SEMARANG PROGRAM STUDI MANAJEMEN - Safari, Teti; Heridiansyah, Jefri; Susetyarsi, Theresia; Marhamah, Marhamah (Sekolah Tinggi Ilmu Ekonomi Semarang, 2022)
The purpose of this study was to determine the effect of self-efficacy, risk tolerance, and freedom in work on the entrepreneurial interest of STIE SEMARANG students in the Management Study Program. The population in this study was STIE SEMARANG students from the Management Study Program while the sample in this study was 45 students or respondents. The results of the study based on the results of the t-test there was an effect of self-efficacy (significance value 0.001) on entrepreneurial interest. The results of the t test have the effect of risk tolerance (significance value 0.004) on entrepreneurial interest. And the results of the t test have the effect of freedom in work (significance value 0.003) on entrepreneurial interest. Based on the F test, it is obtained that the value of Fcount: 23,726 > Ftable 2.83 with a significance of 0.000 <0.05, it can be concluded that the model is a fit model. The coefficient of determination (R2) shows that 63.5% variation in changes in the dependent variable (Interest in Entrepreneurship) can be explained by the independent variables (Self Success, Tolerance of Risk, and Freedom at Work).